Characteristics of Patients With Rheumatoid Arthritis in Turkey: Results From the Turkish League Against Rheumatism Rheumatoid Arthritis Registry - Ece AYDOĞ,; Elem İNAL,; Neşe ÖLMEZ,; Erkan KOZANOĞLU,; Öznur ÖKEN,; Sumru ÖZEL,; Ümit DÜNDAR,; Ayşen AKINCI,; Cihat ÖZTÜRK,; Konçuy SİVRİOĞLU,; Mehmet Tuncay DURUÖZ,; Hatice UĞURLU,; et al. (Archives of Rheumatology, 2015)
Objectives: This study investigates the demographic and clinical characteristics of patients with rheumatoid arthritis (RA) in Turkey, and attempts to identify strategies for the prevention, treatment, and support of RA. Patients and methods: A total of 2,359 patients (1,966 females, 393 males; mean age 51.6±12.5 years; range 18 to 75 years) with RA from 36 centers across Turkey, who were recorded in the Turkish League Against Rheumatism (TLAR) RA Registry between September 2007 and March 2011, were evaluated. Patients’demographic and clinical data were recorded. Disease activity, functional status, and radiographic damage were measured using the Disease Activity Score 28, the Health Assessment Questionnaire, and van der Heijde modified Sharp scoring method. Results: The mean duration of academic education received was 5.2±3.8 years, and 74.6% of the patients were homemakers. Non-biological disease modifying anti-rheumatic drugs were used by 91.0% of the patients, while 10.2% used biological disease-modifying anti-rheumatic drugs. The mean Disease Activity Score 28, Health Assessment Questionnaire, and Sharp scores were 4.0±1.4, 0.38±0.37, and 31.2±57.1, respectively. Of the patients, 17.8% were in remission and 14.1% had low disease activity rates, while 42.7% and 25.5% had moderate and high disease activity rates. Conclusion: The majority of patients with RA in Turkey are middle-aged homemakers. Despite the high rates of disease-modifying anti-rheumatic drugs use, the majority of patients had moderate and high disease activity. These findings indicate that treatment needs of RA patients are not met sufficiently.